PENGEMBANGAN PERANGKAT PEMBELAJARAN DENGAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN LITERASI BAHASA DI SEKOLAH DASAR - Rosyidi, Himawan; Budi Waluyo; Juhana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT Language literacy skills are one of the skills in language learning that are very important for students to have. However, in fact, the level of language literacy skills of students, especially in learning Indonesian, is still relatively low, so quality learning is needed. The purpose of this study was to determine the characteristics, practicality and effectiveness of learning from the development of learning devices through the PjBL model to improve language literacy in elementary schools. The procedures in this study consisted of planning, implementation, and assessment. The sample in this study were fifth grade students of SDN Banjaranyar 03 as the experimental class and fifth grade students of SDN Banjaranyar 02 as the control class. The research instruments consisted of learning devices, observation and assessment instruments. Qualitative data collection was carried out by interviewing research subjects, questionnaires /observations and documentation. While quantitative data were collected by conducting a language literacy ability test. Data analysis techniques include learning quality analysis to analyze the validity, practicality of learning devices, implementation and learning assessment results. Quantitative data analysis includes normality tests, homogeneity, average similarity, and hypothesis testing. Qualitative data analysis was carried out through 4 stages, namely data of validity,reduction, presentation, and drawing conclusions. The results of the study showed that the average value of the validity of the learning device reached 80.89% (good), the average value of practicality 81.50% (good) and the average effectiveness of learning implementation reached 85.98% (very good). From the hypothesis test, the results showed that the language literacy skills of students through the PjBL learning model achieved classical completeness of more than 75%, the average value of students' literacy skills in learning using the PjBL model exceeded the KKM, the proportion of students' language literacy skills in the experimental class was better than the control class, the average language literacy skills of students in the experimental class were better than the control class, the average increase in students' language literacy skills in the experimental class was greater than the control class. It can be concluded that learning with the PjBL model is quality learning in improving students' language literacy skills.